Uma abordagem comportamental para inserção de robôs em ambientes culturais - Antunes, Viviane André (2004)
In this work, we propose methodologies and computer tools to insert robots in cultural environments. The basic idea is to have a robot in a real context (a cultural space) that can represent an user connected to the system through Internet (visitor avatar in the real space) and that the robot also have its representation in a Mixed Reality space (robot avatar in the virtual space). In this way, robot and avatar are not simply real and virtual objects. They play a more important role in the scenery, interfering in the process and taking decisions. In order to have this service running, we developed a module composed by a robot, communication tools and ways to provide integration of these with the virtual environment. As welI we implemented a set of behaviors with the purpose of controlling the robot in the real space. We studied available software and hardware tools for the robotics platform used in the experiments, as welI we developed test routines to determine their potentialities. Finally, we studied the behavior-based control model, we planned and implemented alI the necessary behaviors for the robot integration to the real and virtual cultural spaces. Several experiments were conducted, in order to validate the developed methodologies and tools